Pengaruh Likuiditas dan Leverage terhadap Kebijakan Dividen dengan Ukuran Perusahaan sebagai Variabel Kontrol (Studi Kasus pada Perusahaan Sektor Infrastruktur yang Terdaftar di BEI Tahun 2015-2020) - Syahirah, Nazma; Nazir Ahmad, Gatot; Dalimunthe, Sholatia (CV. Lafadz Jaya, 2023)
with firm size as a control variable (a case study on infrastructure sector companies listed on the Indonesia Stock Exchange in 2015-2020). The data used in this study is an annual report for the infrastructure, utilities and transportation sectors listed on the Indonesia Stock Exchange for the 2015-2020 period. The sampling method used in this study used a purposive sampling technique. From the results of hypothesis testing that has been done, the research results are obtained that liquidity is proxied by current ratio and cash ratio has no effect on dividend policy. Whereas leverage proxied by Debt-to-Equity Ratio (DER) has a significant negative effect on dividend policy.